Under the eagle's wing : a national security strategy of the United States for 2009 - Hart, Gary, 1936- (Speaker's corner books., 2008)
Under the Eagle's Wing provides a sound national security strategy for the new century. Speaking from experience-the former senator was part of the commission that predicted the events of 9/11-Gary Hart makes a compelling plea for the United States and other nations to find strength through a united approach.